2018
DOI: 10.1128/jcm.00367-18
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Influenza A and B Viruses and Respiratory Syncytial Virus by Use of Clinical Laboratory Improvement Amendments of 1988 (CLIA)-Waived Point-of-Care Assays: a Paradigm Shift to Molecular Tests

Abstract: An accurate laboratory diagnosis of influenza, respiratory syncytial virus (RSV), and other respiratory viruses can help to guide patient management, antiviral therapy, infection prevention strategies, and epidemiologic monitoring. Influenza has been the primary driver of rapid laboratory testing due to its morbidity and mortality across all ages, the availability of antiviral therapy, which must be given early to have an effect, and the constant threat of new pandemic strains. Over the past 30 years, there ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 37 publications
0
85
0
1
Order By: Relevance
“…Without question, the future of rapid, random-access molecular testing is moving closer and closer to the bedside or clinic room. Currently, there are a number of Clinical Laboratory Improvement Amendments (CLIA)-waived molecular tests for Influenza virus, some paired with respiratory syncytial virus, group A Streptococcal pharyngitis and for Chlamydia trachomatis and Neisseria gonorrhoeae (CT/NG) with excellent analytical sensitivity and specificity [51,52]. CLIAwaived means that these tests can be performed outside of a laboratory and by non-laboratory staff such as nurses.…”
Section: Point-of-care Molecularmentioning
confidence: 99%
“…Without question, the future of rapid, random-access molecular testing is moving closer and closer to the bedside or clinic room. Currently, there are a number of Clinical Laboratory Improvement Amendments (CLIA)-waived molecular tests for Influenza virus, some paired with respiratory syncytial virus, group A Streptococcal pharyngitis and for Chlamydia trachomatis and Neisseria gonorrhoeae (CT/NG) with excellent analytical sensitivity and specificity [51,52]. CLIAwaived means that these tests can be performed outside of a laboratory and by non-laboratory staff such as nurses.…”
Section: Point-of-care Molecularmentioning
confidence: 99%
“…The major viral pathogens include influenza virus, respiratory syncytial virus (RSV), coronavirus, adenovirus, and rhinovirus. In children below the age of five, the combined global mortality of only influenza and RSV reaches 300 000 deaths each year 2 . Other respiratory viruses, such as adenovirus and rhinovirus, are associated with lower mortality, but significant morbidity, causing a huge economic burden 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, an evolution in viral diagnostic testing has been seen, all the way from conventional approaches to rapid antigen detection. More recently, highly sensitive nucleic acid amplification tests (NAAT) and point‐of‐care tests (POCT) have been developed 2 …”
Section: Introductionmentioning
confidence: 99%
“…Young et al found Ai-POCIT less sensitive than the Cobas Liat POCIT, using stored UTM samples (5). There has also been an excellent review of rapid tests for influenza recently published (6).…”
Section: Discussionmentioning
confidence: 99%